Magnesium and insulin leaf combination on glucose, low-density lipoprotein and malondialdehyde levels in wistar rats with diabetes mellitus - Astari Nurisani; Mamay Mamay; Ana Hidayati Mukaromah; Purwanto AP (Science Midwifery, 2023)
Diabetes mellitus is a metabolic disease characterized by chronic hyperglycemia due to impaired insulin secretion, insulin receptor sensitivity and/or both. Hyperglycemia can trigger oxidative stress conditions that can increase the risk of micro and macrovascular complications. Preventive efforts need to be done such as giving supplements and traditional therapies that have low side effects, namely magnesium and insulin leaves. This research is experimental type with post test only control group. The samples in this study were 30 male wistar rats weighing 170-300g which had healthy conditions adapted for 7 days, given standard feed and given ad libitum drinking water. The results showed that the glucose level in the treatment group 3 when compared to the negative control group had a percentage decrease of 26.49%. LDL and MDA levels were lower in the combination treatment group of magnesium and insulin leaves when compared to the negative control group. The ANOVA results showed that there was a significant difference between the groups in the glucose test results (p < 0.05), and there was no significant difference between the groups in the LDL and MDA results (p > 0.05). The conclusion of this study was that the best results when compared to negative controls were the combination of magnesium at a dose of 300 mg and insulin leaves at a dose of 300 mg/KgBB had a decreased percentage of LDL levels by 52.38% and MDA levels of 29.11%, while for glucose levels the combination of magnesium doses 300 mg and insulin leaves 75 mg/KgBW had a percentage reduction of 26.49%